Earthwork volumetric estimation via unmanned aerial system application: perception from Penang contractors - Norsyakilah Romelia,; Aimee Atikah Zakaria,; Nurfadzillah Ishak,; Faridah Muhamad Halil,; Muhammad Aizat Afiq Abd Ghapar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Despite the geospatial potential of Unmanned Aerial System, its application in the construction industry is still at an early stage and limited exposure on the application. A survey was conducted to identify the factor of utilization level, their difficulties, as well as the perception associated with this technology. Responses from the Penang Contractors showed that the most common utilization factor is cost expectancy and limited payload and battery life, sensitivity to weather, as well as large volume of the generated data and data loss, as difficulties to utilizing UASs in earthwork volumetric estimation during preliminary stage, deployment stage and post-deployment stage respectively. This study also used a qualitative technique, in which data were gathered via interviews with a contractor. Participant consider all variables affecting the perception except project requirements. By understanding UAS utilization in construction, this study offers a pathway for researchers and professionals to investigate utilization factors, difficulties, and perceptions that may have the most impact on Malaysia’s construction industry. These barriers to UAS utilization in Malaysia’s construction industry will not preclude its use. However, government assistance is critical in encouraging the use of UAS and increasing public awareness in the construction industry.